Do Economists Replicate? - Jörg Ankel-Peters; Nathan Fiala; Florian Neubauer (Institute for Replication (I4R), 2023)
Reanalyses of empirical studies and replications in new contexts are important for scientific progress. Journals in economics increasingly require authors to provide data and code alongside published papers, but how much does the economics profession actually replicate? This paper summarizes existing replication definitions and reviews how much economists replicate other scholars' work. We argue that in order to counter incentive problems potentially leading to a replication crisis, replications in the spirit of Merton's 'organized skepticism' are needed - what we call 'policing replications'. We review leading economics journals to show that policing replications are rare and conclude that more incentives to replicate are needed to reap the fruits of rising transparency standards.
Keywords: A11; C18; 330; replication; replicability; research transparency; meta-science; generalizability; systematic review